Efektivitas Penggunaan SYAM-OK Sebagai LMS Dalam Mendukung Proses Pembelajaran Daring di Prodi Pendidikan Teknik Informatika Dan Komputer Universitas Negeri Makassar - Baharuddin, Nadia; Muhammad Yahya; Muh. Yusuf Mappease (Jurusan Teknik Informatika dan Komputer, 2023)
This study aims to determine the level of effectiveness of using the SYAM-OK LMS in online learning in the Informatics and Computer Engineering Education Study Program. This study used a quantitative approach with a descriptive research type with a total sample of 254 for 2018-2020 class student subjects and 19 samples for lecturer subjects in the Informatics and Computer Engineering Education Study Program, Faculty of Engineering, Makassar State University. The research data were obtained from questionnaires and documentation, while the data analysis technique used was descriptive statistical analysis. Based on the discussion and results of the research that has been done, the use of the SYAM-OK LMS is said to be effective, where the results show that the level of effectiveness of using the SYAM-OK LMS in online learning for students is in the high category with a percentage of 75% in both functional aspects, program aspects, aspects of goals and aspects of ideal conditions, while the level of use of LMS SYAM-OK by lecturers is also in the high category with a percentage of 58%. Thus, the use of the SYAM-OK LMS for students and lecturers in the Informatics and Computer Engineering Education Study Program, Makassar State University has been effective